Peer-group leadership in schools - Bandey, Michael John (Rhodes University, Faculty of Education, Department of Education, 1972)
For a number of years I have wondered why many of the prefects of some of the Grahamstown Schools have not become leaders in the particular sphere into which they chose to go after school. More than one head prefect that I have known has appeared to fade into anonymity after apparently leading his peers at school. I wondered if this was perhaps because at school he was not really a leader but simply an efficient policeman. Conversely, people who were not prefects at school often appeared as leaders in their chosen post-school careers. It seemed as if for some reason the prefect system at the schools concerned did not appreciably aid many pupils to develop their leadership potential or the selection procedures were inefficient. On investigating further I became more and. more interested in this topic until eventually, on discovering that the Rhodes University Education Department had a set of leadership scores, (calculated from a personality test) I undertook this investigation.
Keywords: Leadership; School discipline -- South Africa -- Cape of Good Hope; School management and organization -- South Africa -- Cape of Good Hope; Personality assessment of youth -- South Africa -- Cape of Good Hope